RISK ZONING IN THE CONTEXT OF INSURANCE: COMPARISON OF FLOOD, SNOW LOAD, WINDSTORM AND HAILSTORM - Hanak, Tomas; Korytarova, Jana (Journal of Applied Engineering Science, 2014)
Natural disasters may have a catastrophic impact on the lives of people, company operations and property. The impacts of these disasters fall into the category of natural hazards and belong to standard insurance policies; however, they are problematic from the point of view of the varying degree of risk facing the insured objects in different locations. The objective of this paper is to discuss and assess the potential of applying risks zoning to the Czech Republic on the examples of the selected natural hazards of floods, snow load, windstorm and hailstorm. The assessment is conducted using available statistical data and a severity index. It is concluded that after the flood hazard, it is the combined risk of windstorm and hailstorm which has the biggest potential for the introduction of risk zoning for insurance purposes.